1989
DOI: 10.1037/0022-3514.56.6.988
|View full text |Cite
|
Sign up to set email alerts
|

Structure of act-report data: Is the five-factor model of personality recaptured?

Abstract: We examined the correspondence between the structure of act-report data and 5-factor models emerging from trait-rating data. Twenty categories were selected as markers for the 5-factor model and retrospective act reports were constructed for the target categories: One hundred eighteen men and women comprising 59 dating couples completed self-based and observer-based act reports. Several factor analyses tested different assumptions. Retaining total act performance (TAP) produced a blend of the traditional 5 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 55 publications
(103 reference statements)
2
90
0
2
Order By: Relevance
“…Nonetheless, the AFA has been reasonably successful in delineating acts associated with traits such as dominance, submissiveness, aloofness, gregariousness, impulsivity, social intelligence, creativity, and indeed each of the Big Five dimensions (Amelang, Herboth, & Oefner, 1991;Botwin & Buss, 1989;Buss & Craik, 1983a;Rosero, Luengo, Carrillo-de-la-Peña, & Otero-López, 1994;Willmann, Feldt, & Amelang, 1997). Furthermore, scales constructed by aggregating acts for particular traits into composites have generally correlated well with traditional inventory measures of the traits (Amelang et al, 1991;Angleitner & Demtröder, 1988;Botwin & Buss, 1989;Buss & Craik, 1983a;Rosero et al, 1994). Additional studies have found that act self-reports, although retrospective in nature, can converge with observers' ratings of on-line behavior (Gosling, John, Robins, & Craik, 1998) and retrospective ratings of corresponding traits (Amelang et al, 1991).…”
Section: Act Frequency Approach (Afa)mentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, the AFA has been reasonably successful in delineating acts associated with traits such as dominance, submissiveness, aloofness, gregariousness, impulsivity, social intelligence, creativity, and indeed each of the Big Five dimensions (Amelang, Herboth, & Oefner, 1991;Botwin & Buss, 1989;Buss & Craik, 1983a;Rosero, Luengo, Carrillo-de-la-Peña, & Otero-López, 1994;Willmann, Feldt, & Amelang, 1997). Furthermore, scales constructed by aggregating acts for particular traits into composites have generally correlated well with traditional inventory measures of the traits (Amelang et al, 1991;Angleitner & Demtröder, 1988;Botwin & Buss, 1989;Buss & Craik, 1983a;Rosero et al, 1994). Additional studies have found that act self-reports, although retrospective in nature, can converge with observers' ratings of on-line behavior (Gosling, John, Robins, & Craik, 1998) and retrospective ratings of corresponding traits (Amelang et al, 1991).…”
Section: Act Frequency Approach (Afa)mentioning
confidence: 99%
“…One can also question the AFA's reliance on respondents' ratings of the prototypicality of acts for various traits as the sole basis for selecting acts for assessment purposes, rather than more traditional psychometric criteria such as item-total correlations or external validity. Nonetheless, the AFA has been reasonably successful in delineating acts associated with traits such as dominance, submissiveness, aloofness, gregariousness, impulsivity, social intelligence, creativity, and indeed each of the Big Five dimensions (Amelang, Herboth, & Oefner, 1991;Botwin & Buss, 1989;Buss & Craik, 1983a;Rosero, Luengo, Carrillo-de-la-Peña, & Otero-López, 1994;Willmann, Feldt, & Amelang, 1997). Furthermore, scales constructed by aggregating acts for particular traits into composites have generally correlated well with traditional inventory measures of the traits (Amelang et al, 1991;Angleitner & Demtröder, 1988;Botwin & Buss, 1989;Buss & Craik, 1983a;Rosero et al, 1994).…”
Section: Act Frequency Approach (Afa)mentioning
confidence: 99%
See 3 more Smart Citations